Accumulation of lipofuscin‐like pigments of walnuts (Carya cathayensis) during storage: potential roles of lipid oxidation and non‐enzymatic glycosylation. (22nd February 2014) - Li, Wenjuan; Gao, Haiyan; Fang, Xiangjun; Tao, Fei; Chen, Hangjun; Mu, Honglei; Jiang, Yueming
Abstract BACKGROUND Lipofuscin‐like pigments (LFLP) are considered a hallmark of aging. The intracellular LFLP formation rate is negatively correlated with the life expectancy of cell. In food quality, increase of LFLP not only affects the appearance but also causes loss of nutritional value. RESULTS The accumulation of LFLP increased during storage of all walnuts. LFLP fluorescent intensities of walnuts with 4%, 6%, 12% and 16% moisture at the end of storage were 8.1, 4.8, 4.3 and 2.8 times those at the beginning, respectively. The LFLP accumulation of walnuts with high moisture was found to be negatively correlated with soluble sugars and 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical quenching rate, but positively correlated with the content of hydroxymethylfuraldehyde (HMF). While the LFLP accumulation of walnuts with low moisture had a strong positive correlation with anisidine value, it exhibited high negative correlations with acid phosphatase activity, DPPH quenching rate and tocopherol content. CONCLUSION In walnuts with low initial moisture, lipoxidation products increased markedly during storage and these products might provide the source for LFLP accumulation. On the other hand, in walnuts with high initial moisture, reducing sugars derived from the hydrolysis of soluble sugars might play an important role in initiating the Maillard‐like reaction, leading to LFLP accumulation. © 2014 Society of Chemical Industry